Formação docente no Brasil: elementos das tensões e disputas nas políticas educacionais - Ferreira, Alexandre de Oliveira (2022)
This study deals with policies for teacher education based on disputes and tensions around the conceptions and aspirations for teacher education, with the intention of presenting notes on educational policies. Setting up as research categories the policy that runs through and translates the dominant culture by determining the essence of human formation through the teaching profession; teacher training as relevant in the social transformation movement, which has as its first premise a training that meets the social movement and materializes when constituting new ways to think, act and transform our world; to teaching as a concept that is not only comprehensive, but extends to different spheres in the constitution of the profession. This rises as thematic-categorical axes that structure the research to be carried out, as well as the initial paths that were built, in view of the reasons that explain the problem. The sources for the investigation are the official documents that are highlighted in the research from two understandings, which are: primary and secondary sources. The primary sources are constituted as Resolution nº. 2 of 2015, which establishes the Guidelines for Initial and Continuing Education of Education Professionals (BRASIL, 2015b) and the National Curricular Guidelines for the Initial and Continuing Education of Teachers of Basic Education and National Base Common for the Training of Teachers of Basic Education (BNC-Training and BNC-Continuing Education) (BRAZIL, 2019b, 2020b) and the secondary ones are all historical antecedents of policies for training. The theoretical-methodological foundations that guide this research were chosen because they understand that the object of investigation is understood inside a process in which the teaching profession positions itself in the class struggle for being central to historical dialectical materialism. For all that, dialectical historical materialism offers the opportunity to unveil the objective of the research, which is, in short, to understand the disputes and tensions in educational policies that determine views of the world, man and education which have found space in political reformulations for teaching. The study was constituted through document analysis as a source of research and promotion to reflect the justifications for the actions and thoughts of the project directed, by educational policies in Brazil, to teacher education.